2003
DOI: 10.1001/archopht.121.9.1269
|View full text |Cite
|
Sign up to set email alerts
|

Biological Safety Assessment of Docosahexaenoic Acid Supplementation in a Randomized Clinical Trial for X-Linked Retinitis Pigmentosa

Abstract: Background: In a 4-year placebo-controlled trial to elevate blood docosahexaenoic acid levels in patients with X-linked retinitis pigmentosa (XLRP), the goal was to assess the potential benefit of docosahexaenoic acid supplementation in altering disease progression. However, docosahexaenoic acid (22:63) is a highly unsaturated fatty acid and considered a target molecule for free-radical oxidative damage. Thus, nutritional provision of docosahexaenoic acid might lead to an increase in antioxidant stress. Additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 51 publications
(48 reference statements)
1
25
1
Order By: Relevance
“…Of the eleven articles with a full text review, we excluded seven studies (Bergsma 1977;Berson 2010;Dagnelie 2000;Fex 1996;Sibulesky 1999;Tcherkes 1950;Wheaton 2003). We present the reasons for their exclusion in the 'Characteristics of excluded studies' table.…”
Section: Excluded Studiesmentioning
confidence: 99%
“…Of the eleven articles with a full text review, we excluded seven studies (Bergsma 1977;Berson 2010;Dagnelie 2000;Fex 1996;Sibulesky 1999;Tcherkes 1950;Wheaton 2003). We present the reasons for their exclusion in the 'Characteristics of excluded studies' table.…”
Section: Excluded Studiesmentioning
confidence: 99%
“…Finally, 8 studies informed in 13 articles were included in the present review. [9][10][11][12][13][14][15][16][17][18][19][20][21] Characteristics of studies…”
Section: Resultsmentioning
confidence: 99%
“…12 Except Lee et al which studied Best disease, 18 all included studies are on RP. [9][10][11][12][13][14][15][16][17][19][20][21] They assessed supplements based on vitamin A and vitamin E, 12 docosahexaenoic acid (DHA), 9,10,14,16,18 and the carotenoids lutein, 11,13 and β-carotene. 19 We did not identify eligible studies about other HRDs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…9,10 In an epidemiologic study, 11 patients with a diet high in DHA (a median of 0.10 g/d) were at lower risk of Alzheimer's disease than those who consumed less DHA (median 0.03 g/d; relative risk 0.3, 95% confidence interval 0.1-0.9) after adjustments for sex, race, education, total energy intake and the presence of the ε4 polymorphism of the apolipoprotein E gene, the ApoE ε4 allele. Furthermore, various studies [12][13][14][15] (though not all of them) 16 have indicated that blood concentrations of DHA and other n-3 fatty acids are lower in patients with Alzheimer's-related dementia. Because n-3 fatty acids are readily incorporated in cellular membranes, adverse effects from high consumption are rare.…”
mentioning
confidence: 99%